2023
DOI: 10.3389/fimmu.2023.1125702
|View full text |Cite
|
Sign up to set email alerts
|

From a cell model to a fish trial: Immunomodulatory effects of heat-killed Lactiplantibacillus plantarum as a functional ingredient in aquafeeds for salmonids

Abstract: Paraprobiotics (dead/inactivated probiotics) are promising candidates in functional feeds to promote growth performance, modulate intestinal microbiota and enhance immune response of fish. During industrial production, fish are exposed to several stressful conditions such as handling, sub-optimal nutrition and diseases that can lead to reduced growth, increased mortalities and large economical losses. Such problems can be mitigated by use of functional feeds, leading to more-sustainable aquaculture and improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…The percentage of fish with signs of bacterial damage decreases, and their functional status and general resistance increase. It has also been shown that even the use of killed cultures of lactic acid bacteria has an immunomodulatory effect (Rocha et al 2023). In our experiment, we demonstrated the advantage of Extra Trout AST 45/15 with the probiotic supplement compared to the same feed without the supplement in terms of final mass, absolute and average daily mass gain, relative mass gain, mass accumulation coefficient, and SGR in rainbow trout.…”
Section: Discussionsupporting
confidence: 56%
“…The percentage of fish with signs of bacterial damage decreases, and their functional status and general resistance increase. It has also been shown that even the use of killed cultures of lactic acid bacteria has an immunomodulatory effect (Rocha et al 2023). In our experiment, we demonstrated the advantage of Extra Trout AST 45/15 with the probiotic supplement compared to the same feed without the supplement in terms of final mass, absolute and average daily mass gain, relative mass gain, mass accumulation coefficient, and SGR in rainbow trout.…”
Section: Discussionsupporting
confidence: 56%
“…We hypothesize that the reduced abundance of Aquabacterium after HFD feeding may be associated with immune and inflammatory responses in the gut, but more studies are needed to provide evidence. Interestingly, previous studies have shown Arenimonas to be an environmentally relevant microbe, frequently isolated in iron ore and sewage, and have not described adverse effects on fish [ 73 , 74 ]. However, a reduced abundance of Arenimonas in the gut of zebrafish on a high-fat diet with added sea buckthorn was recently found [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…HK L-137 reduces intestinal epithelial permeability and may enhance intestinal barrier function, but the mechanism of action is largely unknown 28,30,31 . In this study, by using rat small intestinal epithelial IEC-6 cells, we showed for the first time that HK L-137 decreases permeability by activating the ERK pathway and increases www.nature.com/scientificreports/ expression of TJ genes and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HK L-137 has been suggested to enhance intestinal barrier function. For example, it was shown to decrease the permeability of the rainbow trout (Oncorhynchus mykiss) intestinal epithelial cell line (RTgutGC), induce intestinal cell growth by activating gut function in broiler chickens, improve intestinal permeability in obese mouse models of metabolic abnormalities and inflammation, and ameliorate systemic and hepatic inflammation through restoration of the intestinal barrier in humans with overweight 28 31 . However, the mechanism by which HK L-137 improves intestinal barrier function is still unclear.…”
Section: Introductionmentioning
confidence: 99%